PERIWAYATAN HADIS SECARA MAKNA PERSPEKTIF MUHAMMAD AMIN AL-SYINQITHIY - Muhammad Ryan Baihaqi; Muhid, Muhid (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2024)
The debate on the transmission of hadith by meaning is not something new. The root of this issue arose due to statements from the Prophet Muhammad that prohibited it, while in other narrations, the Prophet permitted it. The permissibility of transmitting by meaning is feared to lead to a change in the meaning of the hadith as a consequence of textual changes. Muslim scholars, including Muhammad Amin Al-Syinqithiy, have set conditions and limitations regarding the transmission by meaning and who is allowed to do it. He established these conditions and limitations so that narrators who had difficulty transmitting verbally could narrate so by meaning as a form of facilitation. These conditions and limitations also ensure to prevent narrators who transmit by meaning from being reckless, ensuring the authenticity and originality of the hadith, protecting it from distortion and fabrication. By adopting the title of this research, the researchers aim to understand the legal status of transmitting by meaning and what conditions and limitations apply when doing so. This research uses a qualitative literature-based approach, and based on the findings, the researchers employ a descriptive research method. The result of this research is that the transmission of hadiths by meaning is permissible according to Al-Shinqiti, but there are strict conditions and obligatory limitations that must be fulfilled when transmitting them.